Análise dos temas abordados nos TCCs do curso de Educação Física da Universidade Federal do Pará no campus de Castanhal - GOMES, Jéssica Thaiane Silva (2019)
The present study has the general objective of cataloging the topics of Conclusion of the Physical Education Course of the Federal University of Pará at the Castanhal Campus, from 2004 to 2018. Thus, the following specific objectives are set: (i) concepts and fundamentals of Physical Education; (ii) Demonstrate the characteristics of the Physical Education course at the Federal University of Pará at Campus Castanhal; (iii) Identify the research lines most approached by the Physical Education TCCs of UFPA, Campus Castanhal. The methodology was based on the bibliographical research, with a descriptive and exploratory approach, through a search on literature pertinent to the research and in the virtual library of TCCs of the Physical Education Course of Castanhal UFPA and with documentary analysis, since a analysis of the TCCs of the course. The process of analysis of the collected data was made through the analysis of content of Bardin, through an interpretative, reflexive, analytical and critical reading of the works that composed this study. The data obtained indicate that the most searched lines were classified as "other thematic units", since of the 431 TCCs surveyed, 405 were from other thematic areas, with the following elements: Leisure; Training; Psychology of sport and physical exercise; Education, Health and quality of life; Adapted Physical Education and Inclusion; First aid; Pedagogical axis; and Evaluation Measures in Physical Education.